2022
DOI: 10.3390/machines10121124
|View full text |Cite
|
Sign up to set email alerts
|

Winding Design and Efficiency Analysis of a Nine-Phase Induction Machine from a Three-Phase Induction Machine

Abstract: Multiphase machines are a hot research topic in control theory and industrial applications such as electric cars. However, the availability to buy them in the market is limited or null. For this reason, it is common to rewind it from a three-phase commercial machine. In this context, the aim of this paper is two-fold. First, to introduce a straightforward procedure to rewind a nine-phase induction machine from a three-phase one. For that purpose, a study of the three-phase induction motor was performed, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Generally, one CHB module would technically have states P Mm /m and 0, as it needs to be able to power one phase individually, if the other module fails. However, when the two modules are evaluated as one reliability element, as previously elaborated, the three states are 2P Mm /m, P Mm /m and 0, shown in equations ( 18) and (19).…”
Section: -Level Chbmentioning
confidence: 96%
See 1 more Smart Citation
“…Generally, one CHB module would technically have states P Mm /m and 0, as it needs to be able to power one phase individually, if the other module fails. However, when the two modules are evaluated as one reliability element, as previously elaborated, the three states are 2P Mm /m, P Mm /m and 0, shown in equations ( 18) and (19).…”
Section: -Level Chbmentioning
confidence: 96%
“…A six-phase electric aircraft motor was assessed in [37], resulting in 10.6 kW/kg for active parts (6.4 kW/kg considering total weight). Additionally, Da Rosa and others [11] and Fleitas and others [19] showed that a multi-phase machine may not differ in mass from the three-phase machine and can even have a lower value, due to the lower volume of conductive material required.…”
Section: Proposed Alternative Topologiesmentioning
confidence: 99%